James VI & I
1 online resource
Keywords: "James VI & I: Politics, Government and Religion brings together early career and established scholars with a range of approaches to the reign. Their original, research-based essays on a series of broad and interconnected topics invite us to consider Jacobean kingship afresh. King James VI & I (1566-1625) was the first monarch to rule over the three kingdoms of Scotland, England and Ireland. His practice of kingship--which often so skilfully played upon, and navigated between, the contradictory expectations of his contemporaries--provoked lively debate in his day. Four hundred years after James's death, it still does. This book looks again at some of the hottest of the controversies that still define the historiography of the period. With chapters on James's personal reign in Scotland before 1603, his government of Ireland, corruption, peace-making, and the parliamentary and religious politics of his kingship in England, the contributing authors present new archival discoveries, and more familiar materials and problems are reassessed. This edited collection is a stimulating resource for students and researchers of Stuart monarchy and early modern British and Irish history"--